A Whole Language Reading Intervention: A Case Study - Glavach, Matthew; Pribyl, Warren (Journal of the American Academy of Special Education Professionals, 2018)
The study presents a reading intervention for children having a variety of reading deficits. For this study it was found that most of the children had not responded positively to phonics instruction. Based on brain imaging studies, it has been shown that there are positive changes in the left brains of readers with dyslexia who receive phonemic and phonics training early, thus there has been a strong emphasis on phonemic and phonics training in schools. It is believed that if children receive this instruction early, reading difficulties can be avoided, and children develop into both accurate and fluent readers. The authors see this as valuable, however, they question the continued use of phonics for children who do not respond. While research shows that reading pathways in the right hemisphere register for readers with dyslexia, the authors suggest this could be a strength for a whole language reading intervention. Also, research shows that children with dyslexia are less sensitive to the rhythm of natural speech and that can lead to poor phoneme production and reading failure.